fMRI changes during multi-limb movements in Parkinson’s disease - Chung, Jae Woo; Bower, Abigail E.; Malik, Ibrahim; Martello, Justin P.; Knight, Christopher A.; Jeka, John J.; Burciu, Roxana G. (Frontiers in Human Neuroscience, 2023)
While motor coordination problems are frequently reported among individuals with Parkinson's disease (PD), the effects of the disease on the performance of multi-limb movements and the brain changes underlying impaired coordination are not welldocumented.Functional magnetic resonance imaging (fMRI) was used to examine differences in brain activity during a task that involved the coordination of non-homologous limbs (i.e., ipsilateral hand and foot) in individuals with and without PD.Participants included 20 PD and 20 healthy control participants (HC). They were instructed to generate force in a coordinated manner by simultaneously contracting their ipsilateral hand and foot. PD were tested off their antiparkinsonian medication and on their more affected side, whereas the side in controls was randomized.Although both groups were able to coordinate the two limbs to produce the expected level of force, PD had a slower rate of force production and relaxation compared to HC. Additionally, their globus pallidus and primary motor cortex were underactive, whereas their pre-supplementary motor area (pre-SMA) and lateral cerebellum were overactive relative to HC. Importantly, in PD, the fMRI activity within the pre-SMA correlated with the rate of force decrease.Multi-limb force control deficits in PD appear to be related to widespread underactivation within the basal ganglia-cortical loop. An overactivation of higher-level motor regions within the prefrontal cortex and lateral cerebellum may reflect increased cognitive control and performance monitoring that emerges during more complex motor tasks such as those that involve the coordination of multiple limbs.